Multi-geohazards of Ende city area - Igan Supriatman Sutawidjaja; Sugalang Sugalang (Indonesian Journal on Geoscience, 2007)
http://dx.doi.org/10.17014/ijog.vol2no4.20073The Ende City is a steep mountainous area, of which the height of their peaks are above 1500 m asl. It has the limited extent of plain places, without coastal plains. Due to this condition, large parts of the area are vulnerable to mass-movements mainly debris flows, rock-falls and shallow translational and rotational landslides. On the other hand, Flores Island is a segment of the Banda Arc that contains eleven very active volcanoes and numerous inactive volcanic cones. Two of them, Mount Iya and Mount Kelimutu are included to Ende Regency. The northern foot of Mount Iya is only about 1 km away from the southern outskirts of Ende city. But the presence of Mount Meja and Mount Roja as the barrier, and the orientation of the active crater (K2), the highly explosive eruption of Iya Volcano may not directly endanger the city of Ende. Most pyroclastic flows of previous eruptions and other eruptive material emplaced into the sea, but due to a short horizontal distance between Mount Iya and Ende City, the ejected rock fragments can endanger the city of Ende especially its southern parts. A crack has developed around the active crater (K2) of Iya Volcano. It seems that the crack indicates a major weakness within the volcano, which could result in a giant landslide, entering the sea in future eruptions of Iya Volcano. The kinetic energy which is transmitted through the water may probably generate a tsunami. The Ende City also experienced significant damages in the 1992 earthquake. Luckily this city is located on a solid rock instead of alluvial sediments which can potentially undergo liquefaction.